Analisis Perilaku Model Multi Agen dengan Gangguan - Achmadi, Sentot; Miswanto, Miswanto (CAUCHY, 2013)
This paper discuss multi-agent model of the N-dimensional space with the function of attraction and repulsion. In this model is given the disturbance function which is a bounded function. In this paper also discuss about stationary of each agency and stability of the models use stability of Lyapunov. From the analytical results obtained center of the multi-agent is stationary. Also test the stability with Lyapunov method is obtained that the proposed model is a stable model. Numerical simulation results show that each agent will converges to a region that has a certain distance to the center of the multi-agent model